DUL MULUK THEATER PERFORMANCE FUNCTION IN PALEMBANG CITY (Manifest Function and Latent Function) - Nugroho Notosutanto Arhon Dhony (Universitas Negeri Makassar, 2021)
This study aims to analyze the function of the Dul Muluk Theater Performance in Palembang City. This research is a qualitative descriptive study with data collection techniques, namely observation,interviews and documentation. The object of this research is the function of the dul muluk theatre performance, directed by elyas and also the leader of the Tunas Harapan theater arts group. The subject of this research, the researcher tries to see from two functions, namely the manifest function (visible function) and latent function (covered function). The researcher obtained the data by using observation, interview, and documentation techniques. The data obtained were analyzed using qualitative descriptive analysis by describing the state of the object in the field. The results of the study indicate that there are performance functions, consisting of (personal entertainment, aesthetic presentation, educational facilities, entertainment or spectacle, economy as a means of earning aliving and functioning as a means of ritual which has been described in detail in the results anddiscussion.